Estimation of greenhouse gas emissions and food consumption by students of Universidad national Federico Villarreal - López-Ráez, Luz Eufemia; Dávila-Solar, Luis Alberto; Lazo-Chong, Edwin José; Díaz-Chong, Santiago; Marín-Machuca, Olegario (Edelweiss Applied Science and Technology, 2025)
The objective was to determine the relationship between Greenhouse Gas emissions (GHG) expressed in CO2equivalent (CO2eq) and food consumption by students of Universidad Nacional Federico Villarreal. For this purpose, a survey was conducted among students in 2024 using an online form distributed via Facebook, WhatsApp Web, and email. The form included the Kilometer Food Calculator developed by Gonzalez [1] and Pérez, et al. [2] and GHG values reported by Poore and Nemecek [3]. The most consumed food groups were cereals and flours: men (M) 1.8 kg and for women (W) fruits 1.6 kg. According to Mertens, et al. [4] and Ritchie, et al. [5] the most consumed food was rice: M 2.2 kg and W 1.5 kg; finding that according to the Calculator, the estimated annual CO2eq emissions in kg (M 201.3 and W 212.0 kg) are higher than those determined (M 212.1; W 152.0) by the other authors, observing that when grouping foods, the first instrument yields lower values for other foods: M 0.2 and W 0.41; compared to those obtained from other foods reported by Poore and Nemecek [3]: M 44.8 and W 37.7. Given the variability of food groups, it is necessary to study CO2eq emissions for the foods we consume in the country.